Building The Bridge for Teacher-Parents Collaboration in Enhancing Children Critical Literacy Skills: A Systematic Literature Review - Anggraini, Gian Fitria; Sunendar, Dadang; Damayanti, Vismaia S.; Musthafa, Bachrudin (Proceedings International Conference on Education Innovation and Social Science, 2024)
This study aimed to analyze the impact of collaboration between teachers and parents on enhancing students' critical reading abilities. It examines existing literature on the collaboration between teachers and parents in primary schools, particularly emphasizing critical reading proficiency. A systematic search was conducted across five databases using specific criteria to select studies for further analysis. The findings suggest that collaborative efforts between teachers and parents significantly contribute to advancing and diversifying students' critical reading skills. Various strategies can be employed to facilitate this collaboration. Moreover, teachers and parents alike must enhance their knowledge not only on methods to improve children's critical reading skills but also on understanding each other's perspectives and backgrounds. Further research is essential to grasp these factors comprehensively and to develop and assess the impact of parental or teacher beliefs on children's critical reading abilities. Notwithstanding the existing disparities, the outcomes of this review underscore the potential of teacher-parent collaboration in enriching children's critical reading capability.